Anomalous elastic response of HoBa2-xHoxCu 3O7-? ceramic superconductors - Yahya A.K.; Hamid N.A.; Abd-Shukor R.; Imad H. (2023)
Anomalous elastic response has been observed in superconducting HoBa 2-xHoxCu3O7-? (x = 0 and 0.15) from temperature dependent ultrasonic velocity measurements between 80 and 270 K. Longitudinal velocity of superconducting HoBa2Cu3O 7-? (Tczero ? 89 K) showed an anomaly around 230 K indicating a pronounced lattice stiffening. Superconducting HoBa 1.85Ho0.15Cu3O7-? (T czero ? 70 K) also showed a similar longitudinal velocity anomaly around the same temperature. No anomaly was observed for oxygen-reduced non-superconducting HoBa2Cu3O7-?. Temperature dependent shear velocity profiles and absolute velocity measurements at 80 K are also reported and the influence of oxygen content on elastic properties is discussed. 2004 Elsevier Ltd. and Techna Group S.r.l. All rights reserved.